2020
DOI: 10.19044/esj.2020.v16n6p317
|View full text |Cite
|
Sign up to set email alerts
|

Effet De La Combinaison Régénération Naturelle Assistée (RNA) Et Microdose D’engrais Sur La Production Du Mil (Pennisetum Glaucum (L.) R.Br) Dans Les Zones Agro-Écologiques Du Centre-Sud Du Niger

Abstract: This study aims to identify the optimal microdose of fertilizer in millet production fields, where Farmer Managed Natural Regeneration (FMNR) practices are already carried out. The experiment was carried out in 26 villages practicing RNA, including 10 villages in the strict Sahelian zone, 10 villages in the Sahelo-Sudanian zone and 6 villages in the north-Sudanian zone of south-central Niger. A randomized block device is installed in each village comprising 5 treatments (RNA; RNA + Organic manure (F); RNA + F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Farmers invest in trees mainly to maintain or improve the fertility of their soils and they are very aware of the impact of certain species on fertility, which is confirmed by many studies (Mansour et al, 2013;Camara et al, 2017;Dan Lamso et al 2015a, 2015bZounon et al, 2020;Traoré, 2012;Bodo et al, 2019). The results showed that the practise of FMNR improves chemical fertilizer content, 2012) who reports that organic matter and nitrogen levels are higher in soils under tree canopies than outside.…”
Section: Soil Fertilitymentioning
confidence: 81%
See 1 more Smart Citation
“…Farmers invest in trees mainly to maintain or improve the fertility of their soils and they are very aware of the impact of certain species on fertility, which is confirmed by many studies (Mansour et al, 2013;Camara et al, 2017;Dan Lamso et al 2015a, 2015bZounon et al, 2020;Traoré, 2012;Bodo et al, 2019). The results showed that the practise of FMNR improves chemical fertilizer content, 2012) who reports that organic matter and nitrogen levels are higher in soils under tree canopies than outside.…”
Section: Soil Fertilitymentioning
confidence: 81%
“…The combination of assisted natural regeneration plus organic manure plus NPK mineral fertilizer resulted in the highest millet grain and straw yields in the Sahelo-Sudanian zone (464 ±214 kg/ha for grain and 2126 ±1193kg/ha for straw) (Zounon et al, 2020).…”
Section: Agricultural Yields and Food Securitymentioning
confidence: 99%
“…Improving soil fertility under RNA is one of the primary objectives of natural assisted regeneration. Farmers invest in trees mainly to maintain or improve the fertility of their soils, and the impact of certain species on chemical fertility has been confirmed by several studies (Mansour et al, [21] Camara et al, 2017; Dan Lamso et al [22,23] Zounon et al, [24] Traoré, 2012; Bodo et al, [25] Soil analysis results showed that the content of certain nutrients was much higher in fields under RNA compared with control areas not under RNA. These include C (%), N (%), K (meq/100g) and C/N.…”
Section: Discussionmentioning
confidence: 91%
“…Le témoin se caractérise par un bon rendement en épis (REP) et un nombre élevé en épis (NEP). Cette différence pourrait être liée aux variétés, à la pratique de la RNA et aux conditions pédoclimatiques des zones d'études (Zounon et al, 2020). Aussi, l'un des facteurs qui influenceraient la croissance et le tallage est la densité du mil.…”
Section: Analyse En Composante Principale (Acp)unclassified